This House is Haunted: The Amazing Inside Story of the Enfield Poltergeist by Guy Lyon Playfair - Pilkington, Rosemarie (Journal of Scientific Exploration, 2018)
This House is Haunted is probably the most popular of the late Guy Lyon Playfair’s books. This third edition contains the original text, with minor alterations, a new Preface and three short Appendixes in which he provides some afterthoughts, suggests further reading and lastly, gives a few suggestions as to “What to Do with your Poltergeist.” The Enfield case is one of the longest-lasting and comprehensive visitations of, what I prefer to call, Recurrent Spontaneous Psychokinesis (RSPK) in the literature. I say comprehensive because it involved almost all the known phenomena associated with these outbreaks. These included the usual furniture disruptions, “flying” objects, raps and other sounds, levitations of things and people, pools of water appearing out of nowhere, stones falling from the ceilings and flung at others outside from “many directions,” written messages (on paper, but at least one, spelling “shit” on a wall, in excrement!) dematerialization/rematerialization of objects, spontaneous fires, direct voices and so on. Objects as light as LEGOs were thrown, but a very heavy gas fire iron frame cemented into the brickwork was wrenched from a wall as well.